Deep eutectic solvent pretreatment and green separation of lignocellulose - Yao, Zhengyuan; Chong, Gunhean; Guo, Haixin (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Plant-based waste biomass with lignocellulose as an important component is produced in large quantities worldwide every year. The components of lignocellulose that typically exhibit high utilization value include cellulose and hemicellulose, as well as pentoses and hexoses derived from their hydrolysis. As a pretreatment for the hydrolysis process, delignification is a pivotal step to enhance cellulose/hemicellulose accessibility and achieve high yields of fermentable sugars. Additionally, deep eutectic solvents (DESs) are the most widely used solvents for delignification during biomass fractionation due to their clean and environmentally friendly attributes. DESs dissolve lignin by inducing a large amount of β-O-4 bond cleavage and partial carbon–carbon bond cleavage, retaining cellulose in the solid residue, while most of the hemicellulose is hydrolyzed in DES pretreatment. This article provides a comprehensive review of the influence of DESs in the lignocellulose separation process. Key factors such as lignin removal rate, sugar conversion rate, and product chemical structure are critically reviewed to assess the feasibility of employing DESs for lignocellulose separation.